Deteksi Dini Faktor Risiko Terjadinya Penyakit Tidak Menular - Dyan Kunthi Nugrahaeni; Novie Elvinawaty Mauliku; Teguh Akbar Budiana (Universitas Faletehan, 2023)
The prevalence of non-communicable diseases such as hypertension and Type 2 Diabetes Mellitus (T2DM) continued to increase. The purpose of this study was to early detect the risk factors of non-communicable diseases, such as hypertension and T2DM. The research design used a cross-sectional study. The samples were lecturers and educational staffs at the Faculty of Health Science and Technology, University of Jenderal Achmad Yani Cimahi who were > 35 years, namely 61 people. The sampling technique used systematic random sampling. The data analysis was univariate and bivariate by chi-square test, regression and Pearson correlation. The results showed that there were 39.3% of patients with hypertension and 9.8% of patients with T2DM. The risk factor of hypertension was overweight (p value 0.018), while the risk factors of T2DM were history of diabetes (p value 0.43) and overweight (p value 0.020). Age and Body Mass Index (BMI) were positively correlated with systolic blood pressure and blood sugar levels, meaning that the higher the age and BMI, the higher the blood pressure and blood sugar levels. Controlling the occurrence of hypertension and T2DM can be done by reducing BMI.